10 POINTS FOR THE CORRECT ANSWER PLEASE HELP
![10 POINTS FOR THE CORRECT ANSWER PLEASE HELP class=](https://us-static.z-dn.net/files/d3c/24b373fbadde5c5b6901110affefa4dd.png)
Answer:
Step-by-step explanation:
The Pythagorean theorem says:
[tex]a^2+b^2=c^2[/tex]
where a and b are the two legs of the triangle and c is the hypotenuse. Here, let's say a = 6 and b = [tex]\sqrt{13}[/tex]. We then get the following equation:
[tex]c^2= (6)^2+(\sqrt{13})^2=49[/tex]
So c = 7. Technically, c can also equal -7 since (-7)^2 = 49 as well but that does not apply here because a side length cannot be <0. So 7 is the answer.